Kuskaya: A training program for collaboration and innovation in global health - Chan M.C. (2019)
To solve increasingly complex global health problems, health professionals must collaborate with professionals in non-health-related fields. The Universidad Peruana Cayetano Heredia and University of Washington created the NIH-funded Kuskaya training program in response to the need for transformative global health training for talented graduates from all disciplines. Kuskaya is a 1-year, interdisciplinary training program that teaches Peruvian and US graduates critical skills related to public health research through the design and implementation of a collaborative research project in Peru. Between 2014 and 2018, the program has trained 33 fellows, of which one third were from non-health disciplines. The program is unique because it targets junior trainees from disciplines outside of the health field, the program’s curriculum is adapted to fit the fellows’ backgrounds and professional aspirations, and the structure of the program allows for collaboration within the cohort and encourages fellows to apply for additional funding and pursue advanced degrees. Lessons learned in designing the Kuskaya program include: 1) involving mentors in the fellow selection process, 2) involving fellows in existing lines of research to increase mentor involvement, 3) institutionalizing mentoring through regular works-in-progress meetings and providing mentoring materials, and 4) defining a core curriculum for all fellows while providing additional supplementary materials to meet each cohort’s needs, and evaluating their progress. Kuskaya provides an innovative model for bi-national, global health training to engage and provide a public health career pathway for all professionals.